Education in twelfth-century art and architecture : images of learning in Europe, c.1100-1220 - Cleaver, Laura (Boydell studies in medieval art and architecture., 2016)
"On the facade of Chartres cathedral serene personifications of the arts of grammar, rhetoric, dialectic, music, arithmetic, geometry and astronomy present passers-by with a vision of education as an improving process leading to greater knowledge of God. The arts proved a popular subject in medieval imagery, and were included in manuscripts, stained-glass and luxury metalwork objects as well as on the facades of churches. These idealized figures contrast with many textual accounts of education, in which authors recorded the hardships of student poverty and the temptations of drink and women to be found in the cities where teachers were increasingly establishing themselves. This book considers how and why education was explored in the art and architecture of the twelfth century. Through analysis of imagery in a wide range of media, it examines how teachers and students sought to use images to enhance their reputations and the status of their studies. It also investigates how the ideal models often set out in imagery compared with contemporary practice in an era that saw significant changes, beginning with a shift away from monastic education and culminating in the appearance of the first universities."--